An Empirical Warehouse Layout Design and Optimization Approach for Sri Lankan practitioners - Dissanayake, Sadna Cadjateena; Rupasinghe, Thashika (International Journal of Supply Chain Management, 2020)
Warehousing is a vital function for Sri Lanka, due to its trade-dependency. One of the most critical areas highlighted for development in Sri Lanka is infrastructure, of which warehouse holds a key bearing. This study will extend the theoretical framework of Warehouse Layout Designing published by Dissanayake and Rupasinghe, 2018 by incorporating viewpoints of the Sri Lankan practitioners. A focus group discussion with 5 prominent experts in the industry will be incorporated and extended questioner feedback from 10 other practitioners. This research focuses on bridging the theoretical gaps with respect to the warehouse design and optimization from the Sri Lankan context to fill the following research gaps. (1) Approach in identifying the practitioners and developing the questionnaire (2) Assess the warehouse designers approaches carried out by the practitioners (3) overall constraints within the industries in Sri Lanka.